PEDOMAN INSPEKSI TRANSFORMATOR DISTRIBUSI 50 KVA PADA LABORATORIUM TEKNIK TEGANGAN TINGGI - , DANANG PRASETIO WIBOWO ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Distribution transformers have an important role in distribution of electric power. If there is interference, it can reduce transformer reliability. Some of these disorders are physical damage to the transformer, transformer oil, etc. From the results of physical tests visually, quality oil test and transformer insulation test obtained a value indicating whether the transformer is still feasible to operate or to do repairs. In this final assignment found that the transformer insulating oil dielectric strength is decreased, this decrease could be due to contaminants and water content that contained in the transformer oil.With regular inspections will increase the reliability of the transformer.